GAMIFICATION INTERACTION DESIGN ON EVENT PROMOTION WEBSITE - Tanujaya, Untung
Events are activities held to commemorate important things throughout human life, either individually or in groups related to customs, culture, traditions and religions which are held for specific purposes and involve the community environment which is held at certain times. The purpose of an event is a group of people gathering in a certain place for one specific purpose at a certain time. Promotion is activities with the aim of assisting the sale of a product or service at each place of the sales network. Based on literature studies, independent observation, and questionnaire implementation, it was found that there were still deficiencies of the event promotion website, which was boring and had a clunky and confusing appearance that made it difficult for users to understand the events displayed. This final project solves the existing problems by designing an event promotion interaction design site with a user-centered design approach. This interaction design uses gamification features namely points, badges, events feeds, leaderboards, and progress. The result is a high-fidelity prototype of the event promotion website interaction design that meets the usability goals and user experience goals that have been set based on the problems found. It is determined from the results of prototype testing through usability testing. Usability testing is performed using several parameters, namely the SUS, SEQ, IMI, and NPS questionnaires. The usability goals that must be achieved are efficient and learnability, while the user experience goals that must be achieved are helpful and engaging.